2017
DOI: 10.1590/1413-785220172504168827
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Femur Fractures in the Elderly and Cost to the State of Paraná, Brazil

Abstract: Objectives: To evaluate the incidence and economic impact of femur fractures in the state of Paraná, Brazil. Methods: This descriptive study included men and women ≥ 60 years of age with hip fractures which were treated by the Public Health System in emergency care from January 2010 to December 2014. Data were collected from the DATASUS public health database using filters to select patients; results were presented descriptively and as proportions. The standardized incidence of femur fracture was calculated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
0
4
1
11
Order By: Relevance
“…17,25 However, studies that excluded patients under the age of 60 obtained higher means. [19][20] A study conducted in China showed lower mean weight (58.83±11.01 kg) than that in the present study, which can be related to the physical characteristics of Chinese individuals. Cardiovascular disease, associated with mortality and rehospitalization rates, was the main comorbidity found in this and other similar studies.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…17,25 However, studies that excluded patients under the age of 60 obtained higher means. [19][20] A study conducted in China showed lower mean weight (58.83±11.01 kg) than that in the present study, which can be related to the physical characteristics of Chinese individuals. Cardiovascular disease, associated with mortality and rehospitalization rates, was the main comorbidity found in this and other similar studies.…”
Section: Discussioncontrasting
confidence: 69%
“…The predominance of female patients submitted to femur fracture repair surgery observed in this study is corroborated by other recent studies. 12,[15][16][17][18][19][20] Osteoporosis, falls from standing height as a mechanism of injury, exposure to more house chores, greater prevalence of chronic disease, and more fragile physical structure make the female gender more susceptible to this type of fracture. [21][22][23][24] Regarding mean patient age, similar results have been found by studies that evaluated populations in the same age group as those in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A razão masculino / feminino observada neste estudo de 1: 2,2 foi semelhante a de 1: 2,01 encontrada no Paraná, a de 1: 2,04 encontrada em Joinville e a de 1:1,7 encontrada em estudo similar no Brasil por completo e em Sobral no Ceará (Oliveira & Borba, 2017;Silva et al, 2019;Vasconcelos et al, 2020;Rocha & Ribeiro, 2004). Em pesquisa feita em Salvador na Bahia também foram encontradas proporções semelhantes, 1: 2,55 (Santana et al, 2015).…”
Section: Discussionunclassified
“…no Paraná e na cidade de Joinville, onde houve predomínio de fraturas na raça branca (64,6% e 96,7%, respectivamente) (Oliveira & Borba, 2017;Silva et al, 2019). A prevalência de brancos também foi vista no estudo mineiro (Rocha et al, 2001).…”
Section: Discussionunclassified
“…However, the behavior of the three states is shown to be individual when associated with means of permanence and mortality rate. 18,19,20…”
Section: Discussionmentioning
confidence: 99%